Severe salinity contamination in drinking water and associated human health hazards increase migration risk in the southwestern coastal part of Bangladesh. (15th June 2019) - Rakib, M.A.; Sasaki, Jun; Matsuda, Hirotaka; Fukunaga, Mayumi
Abstract: Bangladesh is a deltaic country and is highly vulnerable to climate change and sea level rise. This study explores population migration risk in relation to communal crisis due to socioeconomic vulnerability, drinking water scarcity, and health threats caused by salinity hazards. For this, we conducted a household questionnaire survey as well as, focus group discussions, key informant interviews, and field observations. To identify the drinking water salinity and migration risk, our theoretical process hypothesizes a new composite indexing approach. Salinity hazards and potable water crises have increased the spread of human diseases and treatment costs, while socioeconomic crisis and poverty are inseparable risks of coastal communities because of frequent cyclone hits. Recently, salinity hazards have added a new dimension to health insecurities and household financial instability. Results showed a high migration risk in the unions of Gabura, Munshigonj, Atulia, Burigoaliny, and Padmapukur (from highest risk to lowest), as these areas exhibit worsening situations with respect to drinking water scarcity, salinity hazards, and health hazards, and their adaptive capacities are significantly low. Furthermore, socioeconomic vulnerabilities to cyclone hits, salinity hazards, and severe drinking water scarcity may soon contribute to increased population migration in response to climate change, sea level rise, and the associated impacts of these trends. To tackle the future mass population migration problem, urgent action is required to improve socioeconomic conditions, and provide alternative sources of potable water and health care facilities. Hard and soft measures must be ensured to reconstruct vulnerable areas impacted by riverbank erosion, flooding, and waterlogging. Additionally, action should be taken to enhance local awareness of coastal disasters, their associated hazardous consequences, and possible mitigation and adaptation measures. Highlights: Salinity intrusion creates a severe drinking water crisis and causes public health problems. Additional health expenditures exert pressure on the economy of disaster-affected coastal households. Population migration risk was estimated using a new migration risk estimation technique. Strong migration risk values were found at the community level.